The liposomal delivery of hydrophobic oxidovanadium complexes imparts highly effective cytotoxicity and differentiating capacity in neuroblastoma tumour cells - Elsa Irving; Aristides D.Tagalakis; Ruhina Maeshima; Stephen L. Hart; Simon Eaton; Ari Lehtonen; Andrew W. Stoker (Nature Publishing Group, 2022)
Oxidovanadium complexes with organic ligands are well known to have cytotoxic or differentiating capabilities against a range of cancer cell types. Their limited use in clinical testing though has resulted largely from uncertainties about the long-term toxicities of such complexes, due in part to the speciation to vanadate ions in the circulation. We hypothesised that more highly stable complexes, delivered using liposomes, may provide improved opportunities for oxidovanadium applications against cancer. In this study we sourced specifically hydrophobic forms of oxidovanadium complexes with the explicit aim of demonstrating liposomal encapsulation, bioavailability in cultured neuroblastoma cells, and effective cytotoxic or differentiating activity. Our data show that four ethanol-solubilised complexes with amine bisphenol, aminoalcohol bisphenol or salan ligands are equally or more effective than a previously used complex bis(maltolato)oxovanadium(V) in neuroblastoma cell lines. Moreover, we show that one of these complexes can be stably incorporated into cationic liposomes where it retains very good bioavailability, apparently low speciation and enhanced efficacy compared to ethanol delivery. This study provides the first proof-of-concept that stable, hydrophobic oxidovanadium complexes retain excellent cellular activity when delivered effectively to cancer cells with nanotechnology. This offers the improved prospect of applying oxidovanadium-based drugs in vivo with increased stability and reduced off-target toxicity.